Differences on children's morals in terms of parenting patterns in social welfare institutions for children orphanages islam Raden Mas Suryowinoto Foundation Yogyakarta - Rahmalia Syifa Miasari; Sutipyo Ru'iya (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Children's morals are something that is very important to pay attention to. Morals are the result of the formation of many things and one of them is parenting. This research highlights the differences in children's morals in terms of their upbringing. This research method is a quantitative comparative approach. This research was carried out at the Orphanage Putra Islamic Children's Social Welfare Institution, with a population of 35 children. Data collection techniques with questionnaires. The data analysis technique used the Kruskal Wallis-test analysis. The results of the Kruskal Wallis-test showed a chi-square value = 2.96 and a significance value of 0.228 or p>0.05. From the results of this statistical test it can be concluded that there is no significant difference in children's morals in terms of their upbringing. This is because children who live in the same orphanage and receive similar care from the same caregiver, even though there are perceptions of differences in parenting styles for children, these differences are not too different.